A new genus and species of the cod fish family Moridae (Order Gadiiformes) from southwestern Taiwan - Ho, Hsuan-Ching (Zootaxa, 2019)
Pterophycis spatium gen. nov. et sp. nov. is described on the basis of two specimens collected from shallow waters of southwestern Taiwan. The new genus can be distinguished from other genera in the family in having genital papilla separated from anus by several small scales, all rays on pelvic fin elongate, and the following combination of characters: light organ present; snout broad and rounded, without shelf-like plate; teeth absent from palatines and vomer; swimbladder with anterior elongate projections that attached to openings at rear of the skull; pelvic fin with 7 rays; first dorsal fin short-based, with 8 rays; and second dorsal and anal fins long-based, their margins not indented.